Análisis logit en la evaluación de la susceptibilidad de T. cinnabarinus Boisduval a un acaricida. (1988)
In order to evaluate the susceptibility of red carmin spider population Tetranvchus cinnabarinus to the commercial product Omethoate (soluble concentrate organic phosphorate), samples were taken in four commercial carnation crops. Susceptibility test were carried out to determine the CL50 in laboratory conditions. Difterence of 1.8 to 3.2 times in the reference population were found. Based upon the level of tolerance to the product the CL50 was determined through 17 generations of inbreeding in absence of applications of the omethoate. From the 81h generation a recovering susceptibility and a significant decrease in the LC50, near LC50 of the reference strain, was demonstrated. The results obtained and the statistical methodology proposed give basic information of the study of susceptibility and management of resistance of T. cinnabarinus to pesticides.